2010
DOI: 10.1051/0004-6361/200913972
|View full text |Cite
|
Sign up to set email alerts
|

Distribution functions for magnetic fields on the quiet Sun

Abstract: The statistical properties of the highly structured magnetic field of the quiet Sun are best described in terms of distribution functions, in particular the probability density functions (PDF) for the flux densities and the angular distribution for the orientations of the field vector. They are needed to test the validity of various MHD simulations, but past determinations have led to contradictory results. A main reason for these difficulties lies in the circumstance that the magnetic structuring continues on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
144
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(169 citation statements)
references
References 41 publications
23
144
1
Order By: Relevance
“…Finally, the degree of spatial coherence of the signals increases with the polarimetric signal. By this we mean that the weakest detected fluxes of the quiet Sun on scales below 1000 km show a very dynamic, intermittent, stochastic, magnetic activity unlike the "deterministic" characterisation of the magnetic structure of sunspots and other active structures formed by the socalled flux tubes (López Ariste et al 2006;Martínez González et al 2010b;Stenflo 2010). Stronger fluxes, but still two orders of magnitude weaker than those of the network regions, may organise at granular scales and form magnetic loops (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the degree of spatial coherence of the signals increases with the polarimetric signal. By this we mean that the weakest detected fluxes of the quiet Sun on scales below 1000 km show a very dynamic, intermittent, stochastic, magnetic activity unlike the "deterministic" characterisation of the magnetic structure of sunspots and other active structures formed by the socalled flux tubes (López Ariste et al 2006;Martínez González et al 2010b;Stenflo 2010). Stronger fluxes, but still two orders of magnitude weaker than those of the network regions, may organise at granular scales and form magnetic loops (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Martínez González et al (2008), a number of works have also argued in favor of an isotropic distribution of magnetic fields in the internetwork. In particular, Asensio Ramos (2009) and Stenflo (2010), employing two different approaches, both concluded that for very weak magnetic fields (B → 0) the distribution becomes isotropic. With our present data we cannot argue against or in favor of this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a new controversy about the angular distribution of the magnetic field vector in the quiet Sun. While some authors (Orozco Suárez et al 2007a,b;Lites et al 2007Lites et al , 2008 found that the magnetic field is mostly horizontal (γ ≈ 90 • ; with γ being the inclination of the magnetic field vector with respect to the observer's line-of-sight), others favor a quasi-isotropic distribution of magnetic fields (Martínez González et al 2008;Asensio Ramos 2009;Stenflo 2010). With a few exceptions (Harvey et al 2007;Lites et al 2008;Martínez González et al 2008), all previous studies were carried out employing data recorded at disk center only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…whether they are created by local dynamo processes. The answer to the long-standing question of whether smallscale magnetic fields are more horizontal or vertical seems to currently depend on the method of analysis, and especially how the noise in Q and U is dealt with (e.g., Lites et al 2008;Asensio Ramos 2009;Stenflo 2010;Borrero & Kobel 2011;Orozco Suárez & Bellot Rubio 2012;Steiner & Rezaei 2012;Martínez Pillet 2013). Because the signals Fig.…”
Section: The Need For Large Aperturesmentioning
confidence: 99%